Peran Pembiayaan Syariah dalam Memberdayakan Usaha Mikro, Kecil, dan Menengah (UMKM) di Sektor Perdagangan - Maulidina Rianti Putri; Aliskan Nazla Sabila; Farrel Al Varo Narendra (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to examine how Islamic financing contributes to the empowerment of micro, small, and medium enterprises (MSMEs), particularly in the trade sector. MSMEs play a crucial role as one of the main pillars of the national economy; however, they continue to face various challenges such as limited access to capital, inadequate managerial skills, and low levels of financial literacy. Islamic financing emerges as a solution by applying fundamental Islamic principles, including the prohibition of usury (riba), fairness, and transparency in all financial transactions.The research employs a descriptive qualitative method based on a literature review from various reliable sources. The findings reveal that Islamic financing, through contracts such as murabahah, musyarakah, mudharabah, and ijarah, not only provides access to capital but also offers mentoring and training programs to help entrepreneurs manage their businesses more professionally.The positive impact of Islamic financing can be seen in the improvement of business performance, increased turnover, and enhanced welfare among MSME actors. Furthermore, this system contributes to the stability of the Islamic banking industry and promotes sustainable national economic growth. Therefore, further development of Islamic financing is necessary to expand its reach and benefit a greater number of small and medium enterprises across Indonesia.